Pengaruh Model Pembelajaran Kooperatif Tipe Formulate-Share-Listen-Create (FSLC) Terhadap Kemampuan Komunikasi Matematika Peserta didik Kelas VIII SMPN 16 Padang - HALIMAH SYAHPUTRI (Jurnal Edukasi dan Penelitian Matematika, 2020)
Mathematical communication skills are important for every student in mathematics learning. However, based on the facts in the field, the communication skills of students grade VIII SMPN 16 Padang is still low. Based on the observations it can be concluded that the implementation of learning is centered on the teacher, so students tend to be passive in learning. One effort that can be done is to implement an active learning model that gives students the opportunity to communicate their ideas both verbally and in writing. The learning model that can be applied is Cooperative Learning type Formulate Share Listen Create (FSLC). The type of the research is quasi experiment and use Static Group Design. Based on the result of data analysis by using t test P-value = 0,026, the conclution is mathematical communication skills of students who learn cooperative model type FSLC are better than those learning with conventional learning.Keywords– conventional learning, cooperatif learning type FSLC, Mathematical communication abilities.